Cell-free layer (CFL) measurements in complex geometries: contractions and bifurcations - Novais, Susana (2014)
In this chapter we discuss the cell-free layer (CFL) developed adjacent to the wall of microgeometries containing complex features representative of the microcirculation, such as contractions, expansions, bifurcations and confluences. The microchannels with the different geometries were made of polydimethylsiloxane (PDMS) and we use optical techniques to evaluate the cell-free layer for red blood cells (RBC) suspensions with different hematocrit (Hct). The images are captured using a high-speed video microscopy system and the thickness of the cell free layer was measured using both manual and automatic image analysis techniques. The results show that in in vitro microcirculation, the hematocrit and the geometrical configuration have a major impact on the CFL thickness. In particular, the thickness of the cell-free layer increases as the fluid flows through a contraction-expansion sequence and that this increase is enhanced for lower hematocrit. In contrast, the flow rates tested in this studies did not show a clear influence on the CFL thickness.